A Split Ring Resonator Dielectric Probe for Near-Field Dielectric Imaging - Dmitry Isakov (Nature Portfolio, 2017)
Abstract A single split-ring resonator (SRR) probe for 2D surface mapping and imaging of relative dielectric permittivity for the characterisation of composite materials has been developed. The imaging principle, the analysis and the sensitivity of the SRR surface dielectric probe data is described. The surface dielectric properties of composite materials in the frequency range 1–3 GHz have been measured based on the magnetic resonance frequency of the transmission loss of the SRR dielectric probe when in contact with the surface. The SRR probe performance was analysed analytically and using full-wave simulation, and predictions showed close agreement with experiment for composite materials with spatially varying dielectric permittivity manufactured by 3D printing. The spatial and permittivity resolution of the SRR dielectric probe were controlled by the geometrical parameters of the SRR which provided flexibility to tune the SRR probe. The best accuracy of the dielectric permittivity measurements was within 5%.